Komunikat . no. 106, 1981 - NSZZ "Solidarność" MKS Ziemi Łódzkiej (MKZ NSZZ "Solidarność" Ziemi Łódzkiej, 1981)
Creation and circulation: During strikes the editors applied a double numeration, continous and for consequtive days of strike, with imprint: warning strike or strike readiness. Some issues pubished more than once a day with the hour of publication. After introduction of the Martial Law publication suspended. Republished in 1989 as the official periodical of the Regional Board.